2020
DOI: 10.3390/ijms21165804
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing Radiation as a Source of Oxidative Stress—The Protective Role of Melatonin and Vitamin D

Abstract: Ionizing radiation (IR) has found widespread application in modern medicine, including medical imaging and radiotherapy. As a result, both patients and healthcare professionals are exposed to various IR doses. To minimize the negative side effects of radiation associated with oxidative imbalance, antioxidant therapy has been considered. In this review, studies on the effects of melatonin and vitamin D on radiation-induced oxidative stress are discussed. According to the research data, both substances meet the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 195 publications
(283 reference statements)
0
35
0
Order By: Relevance
“…Thus, additional antioxidant supplementation could be implemented to neutralize the increased level of reactive oxygen species (ROS) responsible for the RAI-related side-effect occurrences. Although the pathophysiology that underlies the association of RAI with oxidative stress in DTC patients requires further investigation, supplementation with antioxidants may be useful due to their radioprotective effects 20 . Notably, Jafari et al demonstrated the radioprotective effect of vitamin C supplementation in DTC patients ablated with RAI 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, additional antioxidant supplementation could be implemented to neutralize the increased level of reactive oxygen species (ROS) responsible for the RAI-related side-effect occurrences. Although the pathophysiology that underlies the association of RAI with oxidative stress in DTC patients requires further investigation, supplementation with antioxidants may be useful due to their radioprotective effects 20 . Notably, Jafari et al demonstrated the radioprotective effect of vitamin C supplementation in DTC patients ablated with RAI 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the mechanisms of this drug, basic studies on its radioprotective effects have been conducted using cultured cells and experimental animals [ 62 ], but it has not yet been used clinically as a radioprotective agent. In addition, antioxidants such as vitamin C, vitamin D, vitamin E, and melatonin have also been studied for their potential as radioprotective agents [ 11 , 16 , 20 ]. However, they are not as safe as H 2 , because it has been reported that the overdose of these antioxidants increases mortality in systematic reviews and meta-analyses [ 63 ].…”
Section: Prospects Of H 2 As a Radioprotective Agentmentioning
confidence: 99%
“…For instance, the radioprotective effects of many synthetic and natural compounds have been investigated. Cytokines such as granulocyte-macrophage colony-stimulating factor (GM-CSF), interleukin (IL)-1, IL-12, and natural compounds such as vitamin C, vitamin D, vitamin E, melatonin, succinate, alpha lipoic acid, and N-acetyl cysteine (NAC) have been reported to exhibit radioprotective effects in animal studies [ 11 , 12 , 13 , 14 , 15 , 16 ]. Many drugs are in various stages of evaluation, but many are far from being ideal radioprotective agents.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Zubillaga et al proved that adults with T21 are at greater risk of vitamin D deficiency, and the additional supplementation brings beneficial results [38]. Palacios et al showed that vitamin D supplementation is necessary for decreasing the risk of pregnancy-related abnormalities, including pre-eclampsia, preterm birth, decreased birth weight, and other related diseases [35,36,[38][39][40][41][42]. In our study, decreased levels of vitamin D were found among women carrying T21 fetuses, similar to the results received in T21 individuals [41].…”
Section: Main Findingsmentioning
confidence: 99%
“…Palacios et al showed that vitamin D supplementation is necessary for decreasing the risk of pregnancy-related abnormalities, including pre-eclampsia, preterm birth, decreased birth weight, and other related diseases [35,36,[38][39][40][41][42]. In our study, decreased levels of vitamin D were found among women carrying T21 fetuses, similar to the results received in T21 individuals [41]. The data obtained in the study showed decreased 25-OH vitamin D concentrations below the recommended level (<30 ng/mL) [32].…”
Section: Main Findingsmentioning
confidence: 99%